UPAYA PENINGKATAN HASIL BELAJAR SISWA MELALUI STRATEGI PEMBELAJARAN READING GUIDE PADA MATERI PERUBAHAN WUJUD BENDA - Khairuna; Fatma Zuhra; Nanda Safarati (Jurnal Binagogik, 2025)
The study aims to determine the improvement of learning outcomes, teacher and student activities, student responses through the use of Reading Guide on the material of changes in the state of matter. The approach in this study is qualitative, the type of classroom action research. The subjects in this study were 15 students of grade V of SD Negeri 7 Gandapura. Data collection techniques through tests, activity sheets and questionnaires. Data analysis techniques through learning outcome tests, observation tests and response tests. The results of the study showed that the improvement of student learning outcomes through the Reading Guide strategy learning strategy on the material of changes in the state of matter was 60% in cycle I increased to 87% in cycle II. The increase in teacher and student activities on the material of changes in the state of matter through the Reading Guide strategy learning strategy was 64% in action I cycle I and action II cycle I by 73% increased to 85% in action I cycle II and 95% in action II cycle II for teacher activities. While student activities were 64% in action I cycle I and action II cycle I by 73% increased to 85% in action I cycle II and 93% in action II cycle II. (3) an increase in student responses by 75% in the “yes” category while the “no” category was 25%. This means that student responses to the lessons carried out by the teacher on the topic of changes in the state of objects through the application of the Reading Guide strategy in class V of SD Negeri 7 Gandapura were well received by students with an average percentage of 75%.